2022
DOI: 10.1016/j.jaip.2021.11.011
|View full text |Cite|
|
Sign up to set email alerts
|

Specific Targeting of Plasma Kallikrein for Treatment of Hereditary Angioedema: A Revolutionary Decade

Abstract: Hereditary angioedema (HAE) is a rare, chronic, genetic disease that presents with nonpruritic angioedema of the face, extremities, airway (can be life-threatening), genitourinary system, and abdomen. These symptoms can significantly impair daily activities. Hereditary angioedema is classified into HAE owing to a deficiency of functional C1INH (HAE-C1INH) or HAE with normal C1INH (HAE-nl-C1INH). Both type I and II HAE-C1INH result from inherited or spontaneous mutations in the SERPING1 gene, which encodes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…Furthermore, we found that CU06-1004 treatment repressed BK-induced Src kinase and MLC activation. These findings showed that CU06-1004 pre- [38][39][40] However, a drug for HAE that targets endothelial integrity has not yet been developed. Although all currently marketed drugs show efficacy in controlling symptoms, most require IV or subcutaneous injection for administration, which is not only inconvenient to patients but also causes side effects including bleeding, rash, infection, inflammation, and itching at the injection site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that CU06-1004 treatment repressed BK-induced Src kinase and MLC activation. These findings showed that CU06-1004 pre- [38][39][40] However, a drug for HAE that targets endothelial integrity has not yet been developed. Although all currently marketed drugs show efficacy in controlling symptoms, most require IV or subcutaneous injection for administration, which is not only inconvenient to patients but also causes side effects including bleeding, rash, infection, inflammation, and itching at the injection site.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, therapeutic options for HAE have shown notable progress. The major mechanisms of currently marketed drugs are C1‐INH replacement, kallikrein inhibition, BK receptor antagonism, and androgen 38–40 . However, a drug for HAE that targets endothelial integrity has not yet been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive bradykinin production or heightened vascular sensitivity to bradykinin appears to underlie HAE [19 ▪ ,21 ▪ ]. Angioedema in the most common forms of HAE responds to FXIIa-neutralizing antibodies [22], PKa inhibitors [23] and reduction of plasma prekallikrein [24], attesting to the importance of the KKS in the disease process.…”
Section: Disease Processes Involving Factor XIImentioning
confidence: 99%
“…Treatment with icatibant also decreased bradykinin levels in patients with HAE, but changes in plasma bradykinin levels were not directly related to the degree of symptom relief ( 58 ). Working upstream from icatibant, plasma kallikrein inhibitors block the binding site of kallikrein to prevent cleavage of HMW kininogen and subsequent bradykinin release and also reduce further activation of factor XIIa to disrupt the positive feedback loop that would otherwise lead to increased kallikrein production ( Figure 2 ) ( 16 , 33 , 59 , 60 ).…”
Section: Single Pathway Therapiesmentioning
confidence: 99%